An irresistible alliance - Laurens, Stephanie (Laurens, Stephanie. Devil's brood trilogy, 2017)
Lord Michael Cynster, the duke's second son, and Miss Cleome Hendon must join forces to hunt down a hoard of gunpowders secretly carted from Kent to London.